Great expectations - Dickens, Charles, 1812-1870; New Editions ([Hellinikon, Greece] : New Editions, 2008)
The adventures of an orphaned young man in Victorian England who is given a great deal of money by an unknown benefactor to enable him to live as a gentleman, pursuing a good education and fulfilling great expectations
Title from container
Keywords: Young men -- England -- Fiction; England -- Social conditions -- 19th century -- Fiction; England -- Social life and customs -- 19th century -- Fiction